Articulated Actions Plan - PAR: a policy of decentralization of education actions (Research, Society and Development, 2018)
The present paper approaches the Articulated Action Plan that was proposed in 2007 as an instrument to decentralize the Union’s actions and resources to the others federated entities aiming to improve the quality, efficiency and equity in the educational policies implementation. The research is justified by its seek to verify in the official guide documents of the PAR the prescription of the decentralization of educational policies for municipalities proccess. The general aim of this research is to analyze the articulation between the Articulated Actions Plan (PAR) of 2007-2011, National Plan of Education (PNE), and the Education Development Plan (PDE) in the implementation of the decentralization process of educational policies. The study is based on the social research methodology which analyzes the subject from the real concret (RODRÍGUEZ, 2014). The procedures adopted were the analysis of the official documents guiding the PAR and the legislation that instituted it as an educational planning policy, as well as the study of the literature that discusses the decentralization of State actions to the federated units. The partial analyzes shows that the plan has the perspective of consolidating the collaboration regime through democratic management and prioritizes decentralization of the Union actions to municipalities and states, without, but it keeps the control of financial resources. It is concluded that PAR has allowed that the Federal Government actions reach a greater coverage in local policies, contributing to the improvement of education and of the teaching and learning of child, young and adults, because the investments happens directly to the municipalities.